2012
DOI: 10.2217/fon.12.91
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Biopsy for Solid Tumors: A Patient’s Companion for Lifelong Characterization of Their Disease

Abstract: Cancer is currently diagnosed and treated based on the results of a tissue biopsy of the primary tumor or a metastasis using invasive techniques such as surgical resection or needle biopsy. New technology for retrieving cancer cells from the circulation, developed in the last 5 years, has made it possible to obtain a ‘fluid biopsy’ from the bloodstream without the need for an invasive procedure. This technological development makes it possible to diagnose and manage cancer from a blood test rather than from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…A study of imaging CTCs after erythrocytic lysis measured the cross-sectional area of CTCs from ten stage IV prostate cancer patients to be 89 µm 2 , while that of the LNCaP cell line was measured to be 142.9 µm 2 under the same measurement conditions 73 . However, the clinical relevance of CTCs of varying sizes is unclear.…”
Section: Biological Basis Of Physical Enrichment Methodsmentioning
confidence: 99%
“…A study of imaging CTCs after erythrocytic lysis measured the cross-sectional area of CTCs from ten stage IV prostate cancer patients to be 89 µm 2 , while that of the LNCaP cell line was measured to be 142.9 µm 2 under the same measurement conditions 73 . However, the clinical relevance of CTCs of varying sizes is unclear.…”
Section: Biological Basis Of Physical Enrichment Methodsmentioning
confidence: 99%
“…Furthermore, tumor staging did not seem to make a difference in the detection of CTCs in NSCLC (40). The major disadvantage with the HD-CTC assay, however, is the inability to analyze live cells due to the fixing of cells during processing (13).…”
Section: Hd-ctcmentioning
confidence: 97%
“…Based on the presence of cytokeratins on tumor cells, it was shown that the detection of non-tumor specific epithelial cell mRNA transcripts, such as cytokeratin, by real-time reverse transcriptase polymerase chain reaction (RT-PCR) was sensitive and could be used to prognosticate early stage breast cancer (10,11). However, the risk of illegitimate transcription (12) of epithelial protein transcripts by nonepithelial cells rendered this approach problematic, as even low levels of illegitimate transcription in the setting of the high ratio of hematopoietic cells to tumor cells would raise enough background noise to interfere with the accuracy of the assay (13). More recently, nucleic acid based detection of tumor DNA has focused on tumor mutations that are distinct from germ cell DNA and not subject to the problem of illegitimate transcription.…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations